Frontiers in autism research : new horizons for diagnosis and treatment - Hu, Valerie W. (World Scientific, 2014)
This unique book focuses on the emerging and expanding areas of research on autism spectrum disorders (ASD). These areas include investigations of genome-wide genetics and epigenetic contributions, metabolic and immune dysfunction, gene-environment interactions, as well as the role of alternative splicing, RNA editing, and noncoding RNAs in gene regulation. Advances in targeted or personalized therapies and alternative interventions, such as music and art therapy, are also presented. In addition, current research on issues involving adults with ASD, a population that has been sorely neglected in the field of autism, is discussed. Within each chapter, experts will review the current status of autism research in his/her field as well as provide a look at the direction where the field will (or should) be headed over the next five years and discuss the translational (practical) outcomes that are anticipated through this research. Some chapters are devoted to the development of molecular or genetic diagnostics for ASD, and novel therapeutic options that are emerging based upon new biological findings on specific genes, pathways, and metabolic functions disrupted in ASD. These unique features are designed to provide "food for thought" for future studies on autism. Hence, this book will be of value not only to established investigators and students conducting research on autism, but also to the general population especially families of individuals affected by ASDs